Chloe's vegan desserts : more than 100 exciting new recipes for cookies and pies, tarts and cobblers, cupcakes and cakes-- and more! / Chloe Coscarelli - Coscarelli, Chloe
"The first vegan winner of Cupcake Wars--and of any reality cooking show!--Chef Chloe, author of the popular Chloe's Kitchen, brings her signature creativity and fun to the best part of every meal: Dessert!Chloe's fantastic-tasting, beautiful desserts are what first got her national media attention when she wowed the judges on Food Network's Cupcake Wars. And her famous desserts are what her enthusiastic fans always